Client expectations about counseling across four cultures. - Hwang, Won Bae (Farmer) (Animo Repository, 1994)
As a consequence of several diverse socio-cultural factors, the counseling process has evolved not without inherent or external prejudices hovering around its proceedings. Certain preconceptions pave the way for unintended consequences as it relegates the counseling procedure to either something advantageous or without substantial purpose. This study aims to underscore the productiveness and benefit of the said process, and determined if there are significant differences among Americans, Koreans, Taiwanese, and Filipinos. Descriptive design using the survey method was utilized in this study. There were 40 randomly chosen respondents for each cultural group namely, American, Taiwanese, Filipino and Korean high school students. Results of the survey showed that there are significant differences among the cultural groups tested. The Taiwanese generally manifested a higher degree of expectation in the various areas of contention. motivation, Openness and Responsibility, the Taiwanese have significantly higher level of expectations than the Americans, Filipinos and Koreans. Regarding Realism, the Koreans displayed a higher propensity that the other three countries. Regarding Acceptance, Confrontation, Directiveness, Empathy, Genuiness, Nurturance, and Self-disclosure, the Taiwanese have significantly higher level of expectations than the Americans, Filipinos, and Koreans. Regarding Attractiveness, Expertise, Tolerance, Trustworthiness, the Koreans have significantly higher levels of expectations than the other three countries. Regarding Concreteness, Immediacy, and Outcome, there are no significant differences among the four cultures.